Analysis of Students' Thinking Ability in Discovery Learning-Based Worksheets to Improve Mathematical Problem-Solving Ability - Eva Fitriani Sari; Sugeng Sutiarso; Sri Hastuti Noer (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Problem-solving ability is essential in the process of learning mathematics. Looking at students' mathematical problem-solving abilities, which can be seen from the learning outcomes, are still less than the expected average. One of the efforts that can be made to improve students' problem-solving skills is to develop Discovery Learning-based worksheets. This study analysed students' thinking skills to improve their mathematical problem-solving abilities. This study uses a qualitative approach with a case study method that emphasizes real cases. This research was conducted on SMP Negeri 6 Metro class VII students on Quadrilaterals. The research used a purposive sampling technique to study as many as 26 students as subjects. The data analysis process was carried out by describing the results of the analysis of answers in writing and showed the ability to write systematic problem-solving procedures. The study results in show that the developed LKPD is very valid; it can be seen that: (1) the achieving results the high category in the application of the Discovery Learning model, (2) the score of each aspect of problem-solving in mathematics has increased, (3) the final test average score has increased, and (4) the score of each problem-solving indicator in mathematics has increased. This can be seen based on the test, and the results show a significant difference between the average increase in learning outcomes in the experimental class using discovery learning-based worksheets and the control class that does not use discovery learning-based worksheets. So it can be concluded that the developed LKPD based on discovery learning is valid, practical, and effective for improving students' mathematical problem-solving abilities.